2011
DOI: 10.1108/00035591111167749
|View full text |Cite
|
Sign up to set email alerts
|

Laser surface treatment to inhibit observed corrosion of reinforcing steel in sulphate: alkaline media

Abstract: Purpose -The effect of chlorides on corrosion of reinforcing steel is well documented in the literature. However, few studies have focused attention on the effect of sulphates on the corrosion of low carbon steel in alkaline media. This paper aims to address this issue. Design/methodology/approach -This paper describes the results of the investigation into the corrosion behaviour of low carbon steel (typically used as reinforcing steel), exposed to alkaline media at a pH of 9 and 12 with varying concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Chloride ion and sulfate radical are the major ingredients of soluble salt, and can directly accelerate the cavitation of metal. Research reveals that corrosion weight loss of carbon steel in alkaline soil is almost in direct proportion to the addition of chloride ion and sulfate ion 56 57 . Researchers such as Lee found that SO 4 2− could hinder the generation of corrosion, but boost the development of corrosion pits that have been formed 58 .…”
Section: Resultsmentioning
confidence: 99%
“…Chloride ion and sulfate radical are the major ingredients of soluble salt, and can directly accelerate the cavitation of metal. Research reveals that corrosion weight loss of carbon steel in alkaline soil is almost in direct proportion to the addition of chloride ion and sulfate ion 56 57 . Researchers such as Lee found that SO 4 2− could hinder the generation of corrosion, but boost the development of corrosion pits that have been formed 58 .…”
Section: Resultsmentioning
confidence: 99%
“…Reported results [54] have suggested that in chloride-sulphate solutions (pH = 8), the mild steel did not passivate, and the corrosion resistance significantly decreased; however, the corrosion rate of the stainless steel AISI 315L was twice as low, presenting pitting corrosion influenced by the chloride ions, although this steel was in a passive state. Mass loss and electrochemical tests [55] revealed that sulphate ions could cause the corrosion of reinforcing steel in alkaline media (pH 9-12) and in the presence of chloride ions the attack is more severe, with evidence of pitting corrosion.…”
Section: Change In Time Of the Open Circuit Potential (Ocp)mentioning
confidence: 99%
“…Several papers have been published on the effects of SO 4 2− , but they neglect the influence of hydroxyl concentrations [10][11][12][13][14]. From the evolution of the corrosion potential in Figure 5, it is evident that the depassivation caused by SO 4 2− is sensitive to alkalinity.…”
Section: Effect Of Sulfate Ionmentioning
confidence: 99%
“…Alhozaimy [9] reported that, with the addition of Ca(OH) 2 in a solution of 0.1 M NaOH and 0.175 M KOH, the constitution of passive film changed, and the charge transfer resistance also increased noticeably. Additionally, SO 4 2− may also affect the condition of the steel bar, as indicated by Abd El Hallem and Premlall [10,11], who claimed that SO 4 2− can cause more severe corrosion than Cl − . However, this conclusion was not no experimental evidence supports this point.…”
Section: Introductionmentioning
confidence: 99%